“Mobile phones as an ict resource in English teaching as a foreign language” - Guaigua Chacón, Karla Johanna (2022)
Mobile phones are ICT devices that allow operations such as calls, messages and Internet browsing. The main objective of this study was to describe the perspective of 14-15-year-old students on the use of mobile phones as an ICT resource in the learning of English as a foreign language at 11 de Noviembre Educative Unit. The research is focused on a quantitative-descriptive design, using a deductive method, based on the perspectives of the participants and the survey applied, which helped to collect real information from a general point of view. For data collection, 10 specific questions were designed and applied with their respective multiple-choice answers on the Likert scale. Once the Covid 19 cases were under control, the students returned to classrooms and with the help of the tutors of two parallels A and B, 21 students between the two grades were chosen. The results of the present research show that mobile phones are an important pedagogical resource for teaching and learning English. Mobile phones are also a resource that can be included in any class and not only in English class. At the same time, the issue of distraction was highlighted as the most common problem identified regarding the use of mobile phones in the classroom. In addition, students agreed that the mobile phone had been a useful teaching-learning resource during the quarantine caused by the pandemic disease Covid19 since it made it easier to access any information they need from the mobile phone. In conclusion, this study revealed that mobile phones played a fundamental role during the pandemic isolation, as it was the most used device in virtual classrooms. Therefore, it helped in training language skills, in other words it turned students’ mobile phones into useful educational tools. However, In the present day, with the return to the classrooms, mobile phones have become a distraction, therefore teachers must be trained in the use of these devices as a resource that allows them to carry out efficient teaching tactics in the classroom, using a variety of strategies and implementing some activities to get students to use their cell phones to learn.